2019
DOI: 10.1140/epjc/s10052-019-7003-1
|View full text |Cite
|
Sign up to set email alerts
|

A complementary third law for black hole thermodynamics

Abstract: There are some examples in the literature, in which despite the fact that the underlying theory or model does not impose a lower bound on the size of black holes, the final temperature under Hawking evaporation is nevertheless finite and nonzero. We show that under some loose conditions, the black hole is necessarily an effective remnant, in the sense that its evaporation time is infinite. That is, the final state that there is nonzero finite temperature despite having no black hole remaining cannot be realize… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 85 publications
(120 reference statements)
0
11
0
Order By: Relevance
“…In a previous study by the authors, a "complementary third law" was found [65], which states that if the end state of black hole evaporation has finite nonzero temperature but zero size, then the evaporation time (assuming thermal evaporation always holds) is necessarily infinite. It was shown therein that GHS black hole with electrical charge held fix, behaves in this way.…”
Section: Discussion: Cosmic Censorship Always Holds Under Hawkingmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study by the authors, a "complementary third law" was found [65], which states that if the end state of black hole evaporation has finite nonzero temperature but zero size, then the evaporation time (assuming thermal evaporation always holds) is necessarily infinite. It was shown therein that GHS black hole with electrical charge held fix, behaves in this way.…”
Section: Discussion: Cosmic Censorship Always Holds Under Hawkingmentioning
confidence: 99%
“…In a previous study by the authors, a "complementary third law" for black hole thermodynamics was found [65]. It states that for a large class of black holes whose end state has finite nonzero temperature but zero size, the evolution time is necessarily infinite (as opposed to the usual third law, which states that the evolution towards zero temperature takes an infinite time).…”
mentioning
confidence: 99%
“…However, to get a precise lifetime one has to compute the grey body factors of all the particles [46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63]. On the other hand, near the end of the evaporation, effective field theory starts to fail, and quantum gravity effect may stop the evaporation, leaving a black hole "remnant" [64][65][66][67]. We hope to be able to consider these questions in our future work.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…More recently, non-commutative geometry [46] and corpuscular gravity, were also shown to give rise to negative α [47]. See [48][49][50], as well as the recent review [51], for more discussions. Incidentally, the method used in Sec.…”
Section: The Sign Of Extended Uncertainty Principle Parametermentioning
confidence: 97%